2020
DOI: 10.1042/bsr20191672
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin fold modifier 1 activates NF-κB pathway by down-regulating LZAP expression in the macrophage of diabetic mouse model

Abstract: Inflammatory response is closely related with the development of many serious health problems worldwide including diabetes mellitus (DM). Ubiquitin-fold modifer 1 (Ufm1) is a newly discovered ubiquitin-like protein, while its function remains poorly investigated, especially in inflammatory response and DM. In the present study, we analyzed the role of Ufm1 on inflammatory response in DM, and found that the proinflammatory cytokine levels (tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6) and IL-1β) and Ufm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 41 publications
2
18
0
Order By: Relevance
“…Given the role of UFMylation in maintain ER homeostasis and in participating in the ER stress response, it is unsurprising that UFM1 is involved in ER-phagy as well [ 38 ]. These findings consolidate that UFM1 expression levels are upregulated in response to ER stress while perturbation of the UFMylation system induces UPR, thus connecting UFMylation rather unsurprisingly to various diseases including cancer, type 2 diabetes (T2D), cardiovascular diseases, and alcoholic hepatitis [ 31 , 33 , 75 , 80 , 83 , 84 , 85 ].…”
Section: Biological Function Of Ufmylationmentioning
confidence: 59%
See 2 more Smart Citations
“…Given the role of UFMylation in maintain ER homeostasis and in participating in the ER stress response, it is unsurprising that UFM1 is involved in ER-phagy as well [ 38 ]. These findings consolidate that UFM1 expression levels are upregulated in response to ER stress while perturbation of the UFMylation system induces UPR, thus connecting UFMylation rather unsurprisingly to various diseases including cancer, type 2 diabetes (T2D), cardiovascular diseases, and alcoholic hepatitis [ 31 , 33 , 75 , 80 , 83 , 84 , 85 ].…”
Section: Biological Function Of Ufmylationmentioning
confidence: 59%
“…Corroborating its role in modulating transcription, UFM1 has been implicated in orchestrating cellular signal transduction pathways such as the NF-kB and JNK signaling cascades [ 83 , 96 , 97 ]. Initial studies described that both UFL1 and the adaptor protein C53 (CDK5RAP3), reported to function as a tumor suppressor [ 43 , 98 , 99 , 100 ], regulates NF-kB signaling by associating directly with RELA (p65), abolishing its phosphorylation to enhance interaction with HDAC thereby stimulating NF-κb activity [ 47 ].…”
Section: Biological Function Of Ufmylationmentioning
confidence: 99%
See 1 more Smart Citation
“…While the discovery of UFM1 was in 2004, only in the last few years has the importance of this modification begun to appear. An increasing body of evidence connects UFM1 to a wide spectrum of human diseases, including hematopoietic diseases, heart diseases, diabetes, intestinal exocrine disease, schizophrenia, and cancer [ 15 , 53 , 54 , 67 , 68 , 69 , 70 , 71 ]. In parallel, UFM1 has been shown essential for embryonic development, and the prevention of this modification in mice causes severe anemia that leads to the death of the embryo [ 72 ].…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Recently, new ufmylation targets involved in cancer progression [ 16 , 17 ], DNA damage response [ 18 , 19 ], translation machinery [ 20 ] and ribosome functioning [ 13 , 14 ] have been identified. Taking in account the broad range of biological pathways affected by ufmylation, it is not surprising that impaired ufmylation can be connected to many human diseases [ 16 , 21 , 22 , 23 , 24 ] and seems to be essential for embryonic development [ 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%